Midiatização nas relações de trabalho e as práticas de comunicação de grupos organizacionais em dispositivos móveis: o caso Whatsapp - Carvalho, Ana Paula Pinto de (2017)
The process of mediatization in everyday relationships is observed in all spheres of public or private life, with attributes that involve real-time responses, full presence and availability. In the organizational field, there is a need to make the decisions of the professionals increasingly agile in a globalized and competitive economic scenario. In this context, individualized media devices, especially those accessed directly from the mobile phone applications, are adequate. It is in this environment that the present research is inserted, whose objective is to investigate the interactions around groups that bring together employees from organizations through mobile devices, especially WhatsApp, whose informal conversations have been incorporated into the formal processes of the companies. For this, it uses the reflections of theorists such as Stig Hjarvard, Andreas Hepp, Gilles Lipovetsky, Bruno Latour and Marlene Marchiori, besides the presuppositions of Erving Goffman and Michel Foucault for the interpretation of the interactions. As for the analysis of communication practices in this mediated universe, the methodological choice was made by three focal groups, which occurred in the WhatsApp environment. Adopting metalanguage as a methodological protocol, the option proved to be correct, because it contributed to the verification of the results obtained, among them, the incorporation of this apparatus into the daily routine of organizations, the relations of power, control and hierarchy present even in a considered space free and democratic, the adoption of differentiated speech in front of leaders or co-workers and the need to be present even outside the walls of the organization.